ADHD Comorbidity, Behavior, and Tic Severity - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
The association of disruptive behavior with social, adaptive, and family functioning in Tourette syndrome (TS), with and without comorbid attention-deficit/hyperactivity disorder (ADHD), was evaluated in 207 children (144 boys and 63 girls) between the ages of 7 and 18 years, in a study at Yale University School of Medicine, New Haven, CT.